Protective effects of an electrophilic metabolite of docosahexaenoic acid on UVB-induced oxidative cell death, dermatitis, and carcinogenesis - SÖZEN, AHMET ERDİ (My University, 2023)
Docosahexaenoic acid (DHA), a representative omega-3 (ω-3) polyunsaturated fatty acids, undergoes metabolism to produce biologically active electrophilic species. 17-Oxo-DHA is one such reactive metabolite generated from DHA by cyclooxygenase-2 and dehydrogenase in activated macrophages. The present study was aimed to investigate the effects of 17-oxo-DHA on ultraviolet B (UVB)-induced oxidative stress, inflammation, and carcinogenesis in mouse skin. UVB-induced epidermal cell death was ameliorated by topically applied 17-oxo-DHA. Topical application of 17-oxo-DHA onto hairless mouse skin inhibited UVB-induced phosphorylation of the proinflammatory transcription factor, STAT3 on tyrosine 705 (Tyr705). The 17-oxo-DHA treatment also reduced the levels of oxidative stress markers, 4-hydroxynonenal-modified protein, malondialdehyde, and 8-oxo-2′-deoxyguanosine. The protective effects of 17-oxo-DHA against oxidative damage in UVB-irradiated mouse skin were associated with activation of Nrf2. 17-Oxo-DHA enhanced the engulfment of apoptotic JB6 cells by macrophages, which was related to the increased expression of the scavenger receptor CD36. The 17-oxo-DHA-mediated potentiation of efferocytic activity of macrophages was attenuated by the pharmacologic inhibition or knockout of Nrf2. The pretreatment with 17-oxo-DHA reduced the UVB-induced skin carcinogenesis and tumor angiogenesis. It was also confirmed that 17-oxo-DHA treatment significantly inhibited the phosphorylation of the Tyr705 residue of STAT3 and decreased the expression of its target proteins in cutaneous papilloma. In conclusion, 17-oxo-DHA protects against UVB-induced oxidative cell death, dermatitis, and carcinogenesis. These effects were associated with inhibition of STAT3-mediated proinflammatory signaling and also activation of Nrf2 with subsequent upregulation of antioxidant and anti-inflammatory gene expression.
Keywords: Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sitogenetik; Kimya; Biyokimya; Biyoinorganik Kimya; Temel Bilimler; Life Sciences; Molecular Biology and Genetics; Cytogenetic; Chemistry; Biochemistry; Bioinorganic Chemistry; Natural Sciences; Temel Bilimler (SCI); Yaşam Bilimleri (LIFE); KİMYA, ORGANİK; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; Natural Sciences (SCI); Life Sciences (LIFE); CHEMISTRY; MOLECULAR BIOLOGY & GENETICS; CHEMISTRY, ORGANIC; BIOCHEMISTRY & MOLECULAR BIOLOGY; Organik Kimya; Fizik Bilimleri; Klinik Biyokimya; Organic Chemistry; Physical Sciences; Clinical Biochemistry; 17-Oxo-DHA; Dermatitis; Efferocytosis; Photocarcinogenesis; Resolution of inflammation; UVB-induced inflammation